Life cycle inventory and impact assessment for an asphalt pavement road construction—a case study in Brazil - Grael, Paulo F. F. [UNESP]; Oliveira, Luiza S. B. L.; Oliveira, Deborah S. B. L.; Bezerra, Barbara S. [UNESP] (Springer Nature, 2021)
Purpose: Currently, there are no life cycle impact data available on the construction of road infrastructure in Brazil. This study aimed to determine several environmental impacts associated with the construction of an asphalt-paved highway in Brazil using the life cycle assessment approach and road construction data available from two Brazilian highways. The results from this study can potentially raise awareness to the importance of life cycle thinking in road construction in Brazil. Methods: The processes considered within the asphalt road pavement product system were extraction and processing of sand, gravel, and pitch; transportation of these inputs; and machinery use and operation, including direct and indirect emissions, raw materials, and electricity/fuel. Inventories available in Ecoinvent were used, and processes relevant to the Brazilian scenario were selected, with modifications made when necessary. The ReCiPe method was used to calculate the impacts, and for each category a second method was used to verify the results. The impact categories analyzed were global warming potential (GWP), terrestrial acidification potential (TAP), ozone depletion potential (ODP), freshwater eutrophication (FWEP), marine eutrophication (MEP), and freshwater ecotoxicity (FWECP). In addition, an alternative scenario was considered by substituting diesel with biodiesel in the transportation trucks. Results and discussion: Gravel production was the main contributor to TAP (56% based on ReCiPe) and MEP (62%) categories. It was also a significant contributor to the GWP (16%), FWEP (25%), and FWECP (33%) categories. Transport of raw materials was the most impactful process in the GWP (58%), FWEP (55%), and FWECP (52%) categories. Pitch production was the major contributor to the ODP category (57%). The impact from sand production was negligible for all categories. Machinery operation had a small contribution in all impact categories (less than 14%). The different assessment methods used for each category indicated similar percent contributions for all processes considered (gravel, sand, pitch, transport, and machinery). Substitution of diesel with biodiesel caused an increase in the total impact for all categories, except for ODP. Conclusions and recommendations: Gravel and pitch production, as well as raw material transport, were the most impactful processes in road construction. Therefore, strategies to reduce the impacts of road construction projects should focus on these three processes. In particular, investigation of the environmental impact, using a life cycle approach, of substituting gravel and pitch with alternative or recycled materials should be carried out for the Brazilian context.
Keywords: Asphalt pavement; Biodiesel; Comparison of LCIA methods; Life cycle impact assessment (LCIA); Life cycle inventory (LCI); OpenLCA; Road construction